Numerical simulation of horizontal well hydraulic fracturing technology for gas production from hydrate reservoir. (July 2021) - Ma, Xiaolong; Sun, Youhong; Guo, Wei; Jia, Rui; Li, Bing
Highlights: The fracture with high permeability can obviously increase gas production The increase of fracture length from 5 to 20 m has no significant improvement on gas production The gas flow rate of fracture is several orders of magnitude higher than that of reservoir The contribution of fracture to total gas production could reach 82% –92% in different case The stimulation effect of GHBL and TPL is better than that of TPL Abstract: Natural gas hydrates in the Shenhu area of the South China Sea occur in clayey silt sediments, and its occurrence environment has low permeability characteristics, making it difficult to commercialise gas production from gas hydrates. A feasibility study of hydraulic fracturing and horizontal well applied to the hydrate reservoir in China's first offshore hydrate production site to increase gas production from hydrates was done. According to the well logging curve, a numerical model was built by Tough+Hydrate to study the influences of horizontal well location and horizontal fracture length on gas production. It was found that compared with the cases without fracturing, the total gas production of the cases with 5 m horizontal fracture length when the horizontal well was in the middle of the gas hydrate-bearing layer (GHBL), the middle of the three-phase layer (TPL), and the top of free gas layer (FGL) increased by 53.20%, 60.29%, and 16.68%, respectively. However, when the fracture length increased from 5 to 20 m, the gas production increased only by 5.41%, 7.77%, and 2.27%, respectively. This meant that the preferred fracture length in this study was 5 m, which could effectively increase the production and reduce the construction cost. Meanwhile, the promotion effects of horizontal fracture on the gas production of the horizontal well at the top of the FGL was smaller than that in the middle of the GHBL or TPL. However, higher gas production could be achieved when the horizontal well was at the top of the FGL with a fracture length of 5 m during 1 and 3 years of production, which was 2.61 and 1.61 times of that in the middle of GHBL, respectively; however, the total gas production of 10 years when the horizontal well was in the middle of GHBL was comparable to that at the top of FGL when horizontal fracture length was 5 m.